Effectiveness of Thermodynamics Textbooks Assisted by Heyzine Flipbook to Improve Students' Generic Science, Critical Thinking and Conceptual Understanding - Aris Doyan; Wahyudi; Syahrial Ayub; Ahmad Harjono; Susilawati (Postgraduate, University of Mataram, 2024)
Thermodynamics as a science studie something concrete and can be proven mathematically using scientific equations that have been proven to be true, so it is not uncommon for students to think that it is difficult to understand. This is because a high level of understanding is needed to understand the concepts of thermodynamics. The aim of this research is to develop a thermodynamics textbook assisted by Heyzine flipbook which is effective in improving students’ generic science, critical thinking and conceptual understanding. This research is a development researchs (Research and Development) which uses the Thiagarajan 4D development model. The subjects in this study were 26 students of the Physics Education study program at Mataram University who took the thermodynamics course. The data in this study is in the form of product effectiveness data obtained through pre-tests and post-tests given to research subjects. The improvement in students' abilities calculated using the n-gain formula. There was an increase in student abilities after being taught with the thermodynamics textbook assisted by Heyzine flipbook according to the n-gain value of 53.31 with moderate criteria. Heyzine flipbook-assisted thermodynamics textbook is proven effective in improving students' generic science, critical thinking and conceptual understanding.